Evaluation of primary care responsiveness by people with mental illness in Spain - Valle Coronado-Vázquez; María Josefa Gil-de-Gómez; Eva Rodríguez-Eguizábal; Bárbara Oliván-Blázquez; Juan Gómez-Salgado; Rosa Magallón-Botaya; María Antonia Sánchez-Calavera (BMC Health Services Research, 2022)
Abstract Background The health system responsiveness is a concept developed by the World Health Organization that measures patients’ expectations for the non-medical care they receive. The aim of this study is to assess primary care responsiveness as seen by people with mental illness and to analyse the factors associated with poor responsiveness. Methods Cross-sectional descriptive study on 426 people with mental illness who had attended primary care consultations at least once in the previous 12 months. The responsiveness of the health system was determined through the short questionnaire “Multi-country Survey Study on Health and Health Systems Responsiveness”. Differences in responsiveness by sociodemographic characteristics were compared through the Chi-squared test. Logistic regression identified the factors associated with poor responsiveness. Results Overall responsiveness was measured as good by 77.4% of patients, being this probability higher in the domains: dignity, confidentiality, and communication. The most valued domains by people with mental illness were prompt attention (42.4%), dignity (30.1%), and communication (17%). Only prompt attention scored high importance and poor responsiveness. In patients with an income lower than 900 euros per month and low level of studies, the probability of poor confidentiality responsiveness was multiplied by 3 and 2.7 respectively. Conclusions People with mental illness perceive good responsiveness from primary care in terms of dignity, confidentiality, and communication. Prompt attention, as the domain of greatest importance and worst valuation, should be prioritised through the implementation of organisational measures in health centres to reduce waiting times, especially in urban areas.